2018
DOI: 10.1016/j.ajme.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy audit over 10 years in a community hospital in Egypt

Abstract: Background: Practice variation is likely to have an important impact on the effectiveness of endoscopy. Performing regular quality audits allows identification of potential underperformance and consequently can result in significant improvement in endoscopy quality. An annual audit was conducted in a community hospital in Egypt. Aim: The aim of the study was to determine if practice and performance of endoscopy is influenced by a consistent audit process by looking for improvement in completeness of procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…In this study normal endoscopy was more common in dyspeptic patients younger than 55 years with alarm symptoms compared to patients older than 55 years (42% vs 30%) while clinically significant endoscopic findings were more common in patients older than 55 years (70% vs 58%).These findings are consistent with previous sudies of Saba Fakhrieh et al [3], AB Thomson etal [12], Ahmed Gado et al (18), Lopez LH et al [14] and Sanjiv M et al [26] while Wallace MB et al [25] reported that age and sex were significant but weak independent predictors of endoscopic findings. Regarding sex distribution, normal endoscopic finding was more common in female patients (42.47% vs 36.17%) while clinically significant endoscopic findings found more in male patients (63.83% vs 57.53%), these results go with studies of Jung HK et al [22] and Sanjiv M et al [26] revealed that male gender increased the risk for having endoscopic abnormality.…”
Section: Significance Of Endoscopyic Findings In Patients With Dyspepsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study normal endoscopy was more common in dyspeptic patients younger than 55 years with alarm symptoms compared to patients older than 55 years (42% vs 30%) while clinically significant endoscopic findings were more common in patients older than 55 years (70% vs 58%).These findings are consistent with previous sudies of Saba Fakhrieh et al [3], AB Thomson etal [12], Ahmed Gado et al (18), Lopez LH et al [14] and Sanjiv M et al [26] while Wallace MB et al [25] reported that age and sex were significant but weak independent predictors of endoscopic findings. Regarding sex distribution, normal endoscopic finding was more common in female patients (42.47% vs 36.17%) while clinically significant endoscopic findings found more in male patients (63.83% vs 57.53%), these results go with studies of Jung HK et al [22] and Sanjiv M et al [26] revealed that male gender increased the risk for having endoscopic abnormality.…”
Section: Significance Of Endoscopyic Findings In Patients With Dyspepsupporting
confidence: 92%
“…The most common clinically significant endoscopic findings in this study were duodenal ulcer in 18.33% of patients followed by gastritis in 14.17% and esophagitis in 10.33%. Ahmed Gado et al [18] revealed that duodenal ulcer was the most common finding in 15% of patients follwed by esophagitis in 14% then gastritis in 4%. Sumathi B etal [6] showed that duodenal ulcer was the most common finding in 10.9% followed by esophagitis in 5.1%.In the study of Piatek -Guziewicz A et al [27] gastritis was the most common endoscopic lesion followed by esophagitis then peptic ulcer.Vasilliou C [28] showed that chronic gastritis followed by hiatus hernia were most prevalent.AB Thomson et al [12] showed that esophagitis was the most common finding in 43.4% while Ghamar Chehreh et al [1] revealed that the most common finding was gastritis.…”
Section: Significance Of Endoscopyic Findings In Patients With Dyspepmentioning
confidence: 99%
See 3 more Smart Citations